Organizational Loyalty and its Relation to Professional Satisfaction among Teachers in Jerash Governorate - Mohammad , Adnan Mufleh (Dirasat: Educational Sciences, 2020)
This study aims to examine the correlational relationship between organizational loyalty and professional satisfaction among secondary school teachers in Jerash governorate. The researcher used the descriptive correlative method. The study sample consisted of (150) male and female teachers of secondary school in Jerash governorate for the academic year 2018-2019. To achieve the objectives of the study, the researcher used a 2-dimension questionnaire as an instrument for study, where the first dimension was organizational loyalty, and the second dimension was professional satisfaction. The questionnaire was applied to secondary school teachers in Jerash governorate. The study showed that the level of organizational loyalty and professional satisfaction of secondary school teachers in Jerash governorate were medium. The results also showed that there is a statistically significant positive relationship between the degree of organizational loyalty and professional satisfaction among secondary school teachers in Jerash governorate. Reconsidering the incentive, promotion systems, and evaluating the performance of teachers. Further, providing real job opportunities for holders of higher qualifications in government organizations to benefit from their potential. Furthermore, holding training workshops for new teachers, to build a deep knowledge base that helps to deal with their colleagues from the perspective of justice, equality, and equal opportunities.